Building Information Modeling and Building Knowledge Modeling in Project Management - Jasim, Nidal A.; Aljumaily, Hadi S.M.; Varouqa, Ibrahim Farouq; Al-Zwainy, Faiq M. S. (Computer Assisted Methods in Engineering and Science, 2020)
Background: The key element for the success of construction projects in the era of technology and information is knowledge. Knowledge management in the construction sector has become a necessary and vital matter, starting with the planning stage, designing, implementing and ending with operation and maintenance stage. One of the most prominent features of knowledge in the construction sector is the building knowledge modeling (BKM). Problem: Although the design stage is considered one of the most important stages of the construction project in terms of eliciting the knowledge element, designers suffer from poor knowledge management, as well as their inability to exploit the capabilities and benefits of building information modeling (BIM), especially knowledge management. Objective: The main aim of this study is to present a conceptual model that integrates the basic principles of knowledge management with contemporary principles of BIM in the design stage and has the ability to store, classify and share the knowledge generated from past designs into future projects. Methodology: The research methodology is constructed on reviewing the pillars of the proposed conceptual model, namely: BKM parameters, BKM library, and BKM clash detection system, then a hypothetical case to prove the validity of the proposed conceptual model using Basmaya residential complex project in the Republic of Iraq is presented as a case study. Results: New four definitions  are introduced: client knowledge, context knowledge, standards knowledge and technical knowledge. The conceptual model proposed in this study has shown great ability and high efficiency in improving and developing knowledge management in the design stage of buildings and projects. In addition, the knowledge stored in the BKM library can be reused in designing new projects in the future. Novelty: The conceptual model has the ability to update constantly itself over time by sharing the knowledge of designers, suppliers and other stakeholders.